Dampak Dari Trims Agreement Terhadap Perekonomian Domestik Pasca Reformasi: Kajian Pengembangan Hukum - Angga Putra Pratama (Pusat Riset dan Inovasi Nasional, 2023)
This article has a discussion of the impact of the TRIMs agreement for Indonesia. In this article we will discuss the TRIMs agreement, utilization during the transition period, and a series of efforts made by the government to increase investment value. This research uses normative legal research methods, while the approaches used are legislative, sociological and comparative literacy studies approaches. The results of this research show that Indonesia is implementing the TRIMs Agreement, taking it into account during the transition period. The government is trying to increase investment, including legal protection, improving human resources, a conducive investment environment, digital technology, innovative approaches, and simplifying the investment process. Therefore, the recommendation is that the government must strengthen investment regulations and policies that pay attention to the development of society and the business world, as well as increase investment and continue to create a profitable investment climate. With various efforts and good cooperation, investment in Indonesia is expected to reach the point of independence and always have a positive impact on economic growth after the Reformation.